Strategies for a Successful PhD Program: Words of Wisdom From the WJNR Editorial Board. (January 2014) - Conn, Vicki S.; Zerwic, Julie; Rawl, Susan; Wyman, Jean F.; Larson, Janet L.; Anderson, Cindy M.; Fahrenwald, Nancy L.; Benefield, Lazelle E.; Cohen, Marlene Z.; Smith, Carol E.; Topp, Robert; Markis, Natalie E.
Nursing doctoral programs prepare students for research-focused careers within academic settings. The purpose of this Editorial Board Special Article is to provide PhD students and advisors with suggestions for making the most of their doctoral experience. Editorial Board members provide their individual insights on the skills and attributes students must acquire during the course of their doctoral education in order to succeed. The authors provide practical tips and advice on how to excel in a PhD program, including how to select an advisor and a dissertation committee, the importance of attending conferences to increase visibility and develop a network of colleagues, presenting and publishing research while still a student, and balancing work and personal life. Students who take full advantage of the opportunities available to them during the course of their doctoral programs will graduate well prepared to take on the multiple responsibilities of research, teaching, and leadership.